2008
DOI: 10.2134/jeq2007.0148
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Sorbing Materials: Sorption Dynamics and Physicochemical Characteristics

Abstract: The effectiveness of various management practices to reduce phosphorus (P) loss from soil to water can potentially be improved by using by-product materials that have the capacity to sorb phosphorus. This study evaluated the P sorption and desorption potential, and the physicochemical characteristics of various phosphorus sorbing materials. Twelve materials were selected and P sorption potentials ranged between 66 and 990 mg kg(-1). Iron, and calcium drinking water treatment residuals (DWTRs), a magnesium fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…Researchers have recognized water treatment residuals (WTRs) as potential P sorbents (Makris et al 2005, Leader et al 2008. Various Fe, Al and Ca-WTRs form in tap water production when Fe or Al salts or lime are added to remove mineral and organic matter and to precipitate P. In this section, we discuss Fe and Al-WTRs for which metal oxides control P retention.…”
Section: Materials That Exhibit P Adsorption On Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have recognized water treatment residuals (WTRs) as potential P sorbents (Makris et al 2005, Leader et al 2008. Various Fe, Al and Ca-WTRs form in tap water production when Fe or Al salts or lime are added to remove mineral and organic matter and to precipitate P. In this section, we discuss Fe and Al-WTRs for which metal oxides control P retention.…”
Section: Materials That Exhibit P Adsorption On Metal Oxidesmentioning
confidence: 99%
“…However, a release of 25% of total Fe and 95% of total P was recorded at a redox potential of -400 mV and a pH of 4.9. Leader et al (2008) studied the desorption of P from a Fe-WTR in a batch test with 0.01 M KCl solution and found that only about 1% of the previously retained P (0.95 mg g -1 ) was desorbed from the material. In line with this result, Makris et al (2005) observed that only a small percentage of the previously retained P was extracted from Al-and Fe-WTRs in 5 mM oxalate solution.…”
Section: Desorption and Dissolution Testsmentioning
confidence: 99%
“…However, if P additions to soils are then ceased, that DP can then desorb from the substrate for years, becoming a source. Most technologies currently used for the reduction of DP, with the exception of gypsum and soluble forms of aluminum (Al; Al sulfate [Al 2 (SO 4 ) 3 ] or Al chloride [AlCl 3 ]), rely on adsorption as the dominant mechanism for DP removal (Douglas et al 2004;Buda et al 2012;Leader et al 2008). Above pH 5, this even includes soluble Al amendments (Peake et al 2002;Shober et al 2006 revealed by the staining technique used.…”
Section: Discussionmentioning
confidence: 99%
“…However, if P additions to soils are then ceased, that DP can then desorb from the substrate for years, becoming a source. Most technologies currently used for the reduction of DP, with the exception of gypsum and soluble forms of aluminum (Al; Al sulfate [Al 2 (SO 4 ) 3 ] or Al chloride [AlCl 3 ]), rely on adsorption as the dominant mechanism for DP removal (Douglas et al 2004;Buda et al 2012;Leader et al 2008). Above pH 5, this even includes soluble Al amendments (Peake et al 2002;Shober et al 2006 Leaching event ) of gypsum (or any other Ca salt or mineral) is low (a desirable property in soils and PRBs) it does not provide high concentrations of Ca 2+ ions rapidly enough to precipitate all of the DP found in high DP concentration manures before the DP can be removed by rainfall events, particularly since the dissolution of gypsum can only occur while it is wet, not while laying dry on soils between rainfall events.…”
mentioning
confidence: 99%
“…These structures use head pressure generated by elevation or flow control devices to force ditch water through a P sorbing material (PSM). Often these PSM's are byproducts of other industrial processes and they provide a substrate for precipitation with metals and/or adsorption onto metal oxides or hydroxides [9][10][11]. Phosphorus sorbing materials can be applied directly to soil or manure, broadcast into ditches, or used in flowthrough structures [12].…”
Section: Introductionmentioning
confidence: 99%